Youth engagement in agripreneurship in Zimbabwe: report and recommendations - Mukwashi, T.; Mabika, V.; Mokhema, Seipati; Enokenwa Baa, Ojongetakah; Davis, Kristin E. (International Water Management Institute (IWMI), 2024)
Africa has witnessed various initiatives, programs, projects and investments aiming at poverty alleviation, agricultural sector strengthening, and rural income generation. Interventions such as agricultural training and technology adoption have shown promising results, boosting productivity and incomes among smallholder farmers. In Zimbabwe, the Ukama Ustawi (UU) initiative has spearheaded efforts to engage youth in agribusiness, fostering food security and social inclusion. This CGIAR Initiative on Diversification in East and Southern Africa aims to empower millions of vulnerable smallholder farmers to transition from maize-mixed systems to sustainably intensified, diversified, and de-risked agri-food systems. One of the research activities under this initiative is Work Package 5 (WP5): Empower and Engage Women and Youth in Agribusiness Ecosystems. Following landscaping study and dialogue in Zimbabwe and Malawi, UU plans to implement brief, impactful interventions intended to pilot or amplify existing youth agripreneurship interventions in both countries. The intervention will be implemented over a period of six months in Zimbabwe, and it will align with WP5.